Analysis of Volatile Components and Key Aroma Components in Dianhong Congou Black Tea Produced by Variable Temperature Fermentation - WANG Yanyan, LIU Zhiwei, YAN Huiting, LU Jianwei, HE Yamei, GAO Jun, BAI Bing, LU Liping (Shipin Kexue)
One bud with two or three leaves from large leafed trees grown in Yunnan that were plucked in summer were used to manufacture Dianhong congou black tea (DCT) by five variable temperature fermentation processes. To determine the optimal variable temperature fermentation parameters, the volatile components in DCT samples were analyzed by sensory evaluation, gas chromatography-mass spectrometry (GC-MS), odor activity value (OAV) and orthogonal partial least squares-discriminant analysis (OPLS-DA). The results of sensory evaluation showed that DCT fermented at 35 ℃/3 h + 25 ℃/3 h had the strongest sweet and fresh aroma with a slight floral note and scored highest among the five DCT samples. The GC-MS analysis identified a total of 747 volatile metabolites belonging to 16 chemical classes. The total amount of aroma volatiles was in the decreasing order of 35 ℃/3 h + 25 ℃/3 h (286.97 μg/g) > 35 ℃/5 h +25 ℃/1 h (261.14 μg/g) > 35 ℃/2 h + 25 ℃/4 h (253.62 μg/g) > 35 ℃/1 h + 25 ℃/5 h (238.79 μg/g) > 35 ℃/4 h + 25 ℃/2 h (214.44 μg/g). Using the cutoff of OAV > 1, 152 key aroma compounds were identified from the five samples. β-Ionone, linalool and geraniol may contribute to the strong sweet floral aroma of DCT fermented at 35 ℃/3 h + 25 ℃/3 h. In addition, (1S)-2,6,6-trimethylbicyclo[3.1.1] hept-2-ene, α-pinene, piperonal, 1,3,3-trimethyl-bicyclo[2.2.1] hept-2-one, toluene and β-phenylethyl acetate were found to be the key differential aroma components between 35 ℃/3 h + 25 ℃/3 h and the other fermentation processes. In summary, DCT fermented at 35 ℃/3 h + 25 ℃/3 h showed rich varieties and contents of aroma substances. These results provide a reference for processing innovations and quality improvement of DCT.